Personal finance - Rosefsky, Robert S. (New York : John Wiley and Sons, 1999)
This book is divided into five parts: Family Economics; A Roof over your Head; Where the Money is; Making your Money Grow; Protecting what you work for.
Keywords: Finance; Economics; Finance, Personal